Effect of Attentional Focus Strategies on the Biomechanical Performance of the Drop Jump. Issue 3 (March 2019) - Comyns, Thomas M.; Brady, Claire J.; Molloy, James
Abstract : Abstract: Comyns, TM, Brady, CJ, and Molloy, J. Effect of attentional focus strategies on the biomechanical performance of the drop jump. J Strength Cond Res 33(3): 626–632, 2019—Motor performance can be influenced by focusing an athlete's attention through the use of verbal instructions. There is limited research on the effect of internal, neutral, and external attentional focus strategies on drop jump (DJ) performance aimed at maximizing height jumped (HJ) and minimizing ground contact time (CT). The purpose of this study was to assess the effect of attentional focus strategies on biomechanical variables related to efficient DJ performance, namely HJ, CT, reactive strength index (RSI), leg-spring stiffness, and peak and relative peak ground reaction force (GRF). Seventeen male recreationally trained subjects performed 2 DJs after listening to instructions designed to evoke an internal, external, or neutral attentional focus. In total, 6 DJs were performed in the testing session, and the order of the instructions was randomly assigned. Significance was set at p ⩽ 0.05. Results indicated that, compared with the neutral strategy, the external focus resulted in significantly higher RSI ( p = 0.046), peak GRF ( p = 0.025), relative GRF ( p = 0.02), and leg-spring stiffness ( p = 0.02). No significant difference was seen in DJ CT and HJ between all 3 conditions ( p ≥ 0.05). These results indicate that the use of an external focus of attention may potentially result in a more effective and efficient fast stretch-shortening cycle performance because of the augmentation of RSI and leg stiffness. More research is warranted, however, because of the lack of significant results pertaining to CT and HJ.